EXPLORING THE IMPACT OF DIGITAL TECHNOLOGY ON TEACHING PROCESS (International journal of artificial intelligence, 2024)
Digital technologies play an important role in the modern educational process, diversifying teaching methods, developing distance learning, and strengthening an individual approach. This article analyzes the impact of digital technologies on the educational process, their capabilities, and emerging problems. It also highlights the role of technologies in gamification, global communication, and increasing the effectiveness of education. At the same time, it discusses the risks and future prospects associated with their misuse.